Vinaya-piṭaka : 1, Bhikkhu-Pātimokkha, 2, Bhikkhunī-Pātimokkha, 3, Mahāvagga, 4, Cullavagga - Sāṅkrtyāyana, Rāhula, 1893-1963 (SAMP early 20th-century Indian books project ;, 1935)
Vinayapiṭaka, a Theravada Buddhist canonical text.